2020
DOI: 10.2169/internalmedicine.5697-20
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 Complicated by Multiple Simultaneous Intracerebral Hemorrhages

Abstract: The relationship between coronavirus disease 2019 (COVID-19) and intracerebral hemorrhage remains unclear. We herein report a case of severe COVID-19 pneumonia complicated by multiple simultaneous intracerebral hemorrhages (MSICH). The patient died eight days after the episode of MSICH. No apparent coagulopathy was observed; however, extracorporeal membrane oxygenation and anticoagulation might have caused the occurrence of MSICH. Laboratory findings showed hypercoagulability, suggesting that thrombotic etiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“… Primary ICH 0 The diagnosis of COVID-19 was made 7 days after admission with positive PCR test results; subsequent PCR tests were found negative. No COVID-19 symptoms prior admission Motoie et al [39] 1 ICH male 50 NR 1 1 - IV UFH Multifocal Secondary ICH to HT of an ischemic stroke 10 Patient on ECMO.Patient in hypercoagulable state prior to ICH. The patient died 8 days after ICH onset.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Primary ICH 0 The diagnosis of COVID-19 was made 7 days after admission with positive PCR test results; subsequent PCR tests were found negative. No COVID-19 symptoms prior admission Motoie et al [39] 1 ICH male 50 NR 1 1 - IV UFH Multifocal Secondary ICH to HT of an ischemic stroke 10 Patient on ECMO.Patient in hypercoagulable state prior to ICH. The patient died 8 days after ICH onset.…”
Section: Resultsmentioning
confidence: 99%
“…Anticoagulation prior to onset of brain hemorrhage was administered in 88 (75%) out of the 118 patients with intracranial hemorrhage [2] , [18] , [21] – [23] , [27] , [29] – [31] , [33] [35] , [39] , [42] – 48] [49] , [50] , and 54 (75%) of the 72 patients with ICH. [2] , [18] , [22] , [29] – [31] , [33] [35] , [39] , [42] – 48] [49] , [50] The type of anticoagulation treatment was reported in 67 cases with intracranial hemorrhages; in 62 of them anticoagulation treatment was initiated in-hospital (39 received unfractionated heparin (UFH), 16 low molecular weight heparin (LMWH), 4 heparin & argatroban, 3 heparin switched to LWMH), and 5 have been on long term anticoagulant treatment (3 were receiving warfarin, and 2 warfarin/dabigatran). [2] , [18] , [21] , [29] – [31] , [33] [35] , [39] , [42] , [44] , [49] , [50] …”
Section: History Of Arterial Hypertension and Prior Use Of Anticoagulantsmentioning
confidence: 99%
See 1 more Smart Citation
“…of this subgroup analysis is limited by its wide CIs, which reduces the certainty of this finding. Elevated d-dimer and fibrinogen levels found in many of these patients may represent early signs of disruption to the coagulation cascade, and autopsy findings of cerebral vasculopathy further support the role of COVID-19associated endotheliopathy (32)(33)(34). Recent studies demonstrated benefit of therapeutic anticoagulation in patients with moderate COVID-19 infections, but this benefit was not seen in critical or severe COVID-19 infections (43,44).…”
Section: Discussionmentioning
confidence: 91%
“…caused by this disease [16,[18][19][20][21], such events in young otherwise healthy individuals with no preexisting cerebrovascular lesions or not receiving the aforementioned therapies remain rare. Patients on ECMO have formerly demonstrated high rates of intracranial hemorrhage due to the complex adjustment of anticoagulation needed to maintain appropriate oxygenation, even in the presence of other viral respiratory diseases [22][23][24].…”
Section: Limitationsmentioning
confidence: 99%